CClinical determinants associated with prolonged length of stay in patients hospitalized with multiple myeloma - Guerra Angel, Roger Javier; Becerra Caicedo , Katherine; Luna Murillo , Vanessa (Interdisciplinary Journal of Epidemiology and Public Health, 2023)
Introduction: Multiple myeloma is a hematologic cancer associated with low incidence, but high rates of illness and substantial hospital burden for health systems; the importance of identifying factors that may be predictors of prolonged length of stay (LOS) is vital for resource planning, decision-making, and improvement of clinical management in cancer. Objective: To estimate the clinical determinants that predict prolonged length of stay in hospital admissions of patients with multiple myeloma. Methods: Analytical observational study of cases and controls, which included patients with Multiple Myeloma hospitalized between 2017 to 2021. Admissions with LOS longer than 14 days (referring to NIH, USA) were identified cases and LOS lower were identified controls. Nominal and categorical descriptive statistics were performed with a multivariate analysis using logistic regression to estimate predictive clinical determinants of prolonged LOS and sensitivity analysis with ROC curve. Results: Were included 391 hospital admissions with 150 cases and 241 controls, corresponding to 223 patients. Infections (OR: 1.74; IC:1.12-2.71), hydroelectrolytic and metabolic disorders (OR: 2.1; IC: 1.28-3.45), nutritional deficiencies (OR: 2.7; CI: 1.6-4.8), and psychiatric disorders (OR: 20.5; CI: 1.14-3.69) were presented as predictive risk factors for prolonged LOS in hospitalized patients with multiple myeloma. Conclusion: Infections hydro-electrolyte imbalance, metabolic disorders, nutritional deficiencies and psychiatric disorders were the factors related to prolonged hospital stay.